Preparation and Application of Monoclonal Antibodies Targeting IgM in Pearl Gentian Grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) - Xiaorui Qian; Jiong Wu; Jiamin Qiu; Yixin Li; Jialin Zhang; Xiaoli Xu; Yinan Wang; Qiang Li (Fishes, 2026)
Viral and bacterial pathogen pathogens cause disease outbreaks that challenge the pearl gentian grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) industry’s sustainable development. The lack of monoclonal antibodies (mAbs) targeting serum immunoglobulin M (IgM) in this hybrid grouper impedes the development of non-lethal immunoassays for detecting pathogen infections, as well as research on immune responses following vaccination. We purified serum IgM from hybrid pearl gentian grouper and generated two mAbs—designated 41-H2-E1 and 62-E8-G9—against the purified IgM, finding that mAb 62-E8-G9 specifically recognized the IgM heavy chain, whereas mAb 41-H2-E1 specifically recognized the light chain. In indirect immunofluorescence assays, both mAbs reacted with surface Ig-positive (sIg+) lymphocytes. A double-antibody sandwich ELISA was subsequently established using mAb 62-E8-G9 as the capture antibody and HRP-conjugated mAb 41-H2-E1 as the detection antibody, enabling accurate quantification of serum IgM levels. Significant differences in IgM concentrations were observed between larger and smaller individuals (9.11 μg/mL vs. 3.84 μg/mL, p